Implementasi Program Penguatan Pendidikan Karakter (PPK) Dalam Pembelajaran Pendidikan Agama Islam (Studi Deksriptif di SD Rusyda Medan) - Haidir Haidir; Media Gusman; Nona Kumala Sari (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
This study aims to analyze (1) implementation of character education strengthening programs in learning, (2) Implementation of character education strengthening programs outside of learning, (3) factors encountered in implementing character education strengthening programs in SD Rusyda medan. The research method used is a qualitative research method with a descriptive study approach. The results of the study indicate that SD Ruydda Medan has implemented the provisions of Perpres No. 87 of 2017. In character learning is packaged in the form of material that is explained in harmony with other subject matter. These character values are contained in the teacher learning tool, which is therefore not just insert material, but becomes material that has its own target achievement. Meanwhile outside program learning takes place in activities that involve physical activities such as flag ceremonies, and extracurricular activities such as scouting, arts and martial arts. Constraints faced are the lack of training from the ministry of education on character education strengthening programs, the lack of teacher and parent collaboration on character education.